Effect of Irrigation Water on the Salinity of Agricultural Soils in the District of Pisac, Cusco 2023 - Rojas Manotupa, Erick Ronaldo (2025)
The district of Pisac in the Cusco region, due to its climate, has vast expanses dedicated to agricultural activities, which do not have studies regarding the salinity of its agricultural soils. One issue is that the quality of their agricultural products may be due to soil salinization, where farmers have observed problems in the development of their crops. The physicochemical characteristics, salinity, RAS, and PSI of the irrigation water and agricultural soils have been evaluated during the dry and rainy periods. The soils have shown low salinity and sodium in both periods, ranging for EC from 0.419 to 2.140 dS/m, pH from 7.2 to 7.9, and PSI from 0.57 to 1.47%. Likewise, the soils have shown low fertility, low water retention, and high alkalinity. The irrigation water has shown an EC of 285 to 486 μS/cm and an SAR of 0.36 to 0.65 meq/L, being classified as C2S1, which would affect the corn crops grown in the district of Pisac, with a greater impact during the dry period; and according to the ECA, it is classified as water of quality for irrigation. It has been concluded that the reported problems are being caused by other factors such as inadequate water management, as well as low fertility and slight alkalinity that agricultural soils have shown.